High-performance liquid chromatography-based characterization of fengycin produced by Bacillus amyloliquefaciens against Fusarium graminearum and Rhizoctonia solani - MUDDASIR KHAN; Muhammad Salman; Abdullah (Kuwait Journal of Science)
A substantial loss of crop production worldwide is attributed to fungal phytopathogens. The most important economic pathogens among these fungal phytopathogens are Fusarium graminearum and Rhizoctonia solani, which cause a wide range of plant diseases. The present study is an approach toward bio pesticides, Bacillus amyloliquefaciens was isolated from soil, cultivated for the production of secondary metabolites production, optical density of the growth curve was measured and screened against the most important fungal phytopathogens Fusarium graminearum and Rhizoctonia solani, which was isolated from diseased crops. The secondary metabolites of Bacillus amyloliquefaciens was identified as fengycin by High performance liquid chromatography (HPLC) at 215nm wavelengths. Fengycin was screened at various concentrations (1, 1/2, 1/4, 1/8 and 1/16) against the Fusarium graminearum and Rhizoctonia solani. Various fengycin concentrations have a significant effect (p<0.005) on the growth of Fusarium graminearum and Rhizoctonia solani. The current study concluded that B. amyloliquefaciens secondary metabolites fengycin having high potential to inhibit the growth of F. graminearum and R. solani.